اردو شاعری کا علامتی نظام: THE SYMBOLIC SYSTEM OF URDU POETRY (Al-Aasar, 2025)
Symbolic language is one of the major characteristics of Gazal throughout its history. Urdu Gazal has used different types of symbols extracted from its contemporary social and cultural environment .Same can be seen in modern period of Urdu literature. This article attempts to identify, distinguish and critically analyze the symbols used in modern era of Urdu Gazal. Urdu ghazal, whether ancient or modern, has had symbolism, allegory, and symbolism as its basic features. Poets have used poetic devices such as allusions, metaphors, similes, metaphors, and symbols to create this layering. Thus, most of the words used in high literary expression have symbolic status, but the words used in ghazal poetry are especially characterized by symbolic properties. Dr. Hamid Kashmiri considers symbolism to be a characteristic of poetry rather than its decoration. According to him: “It is certain that the symbolism of poetry can increase the complexity and multifacetedness of the experience, but it is more correct to say that the poetic experience takes on symbolic form as a result of the application of diverse and contradictory elements at the poet’s internal level. As if symbolism is a characteristic of poetry and not its decoration or the style it has developed.